2022
DOI: 10.20944/preprints202205.0221.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ascorbic Acid Effect on Frozen and Thawed on Sperm Motility, Plasma Membrane Integrity, Livability and Acrosome Integrity of Ring-Necked Pheasant (Phasianus colchicus) Semen <strong> </strong>

Abstract: Ring necked-pheasant (Phasianus colchicus) is bird of order Galliformes. Ring necked-pheasant is also known as gallinaceous bird and game bird. It looks like chicken bird. It is national bird of South Dakota. It is mostly found in wild areas but in Pakistan it exists as Domestic bird. It has high proteins and low fat in its meat. The present study was conducted to check the effect of ascorbic acid on sperm Motility, sperm cytoplasmic membrane integrity, sperm livability and acrosome integrity of Ring-necked ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The researcher also stated that the research showed a different result from previous research. This may due to the different species and environment [4]. The results were similar with Al-Daraji [3] that stated addition of 8% tomato juice into chicken semen extender can significantly increase the percentage of live spermatozoa significantly at 0-hour storage time compared to 2%, 4% and 6% of tomato juice supplementation.…”
Section: Individual Motility Viability and Membrane Integritysupporting
confidence: 81%
See 1 more Smart Citation
“…The researcher also stated that the research showed a different result from previous research. This may due to the different species and environment [4]. The results were similar with Al-Daraji [3] that stated addition of 8% tomato juice into chicken semen extender can significantly increase the percentage of live spermatozoa significantly at 0-hour storage time compared to 2%, 4% and 6% of tomato juice supplementation.…”
Section: Individual Motility Viability and Membrane Integritysupporting
confidence: 81%
“…According to Ali et al [4] there was positive effect (P<0.05) on semen of Ring-necked pheasant by using 3mM of ascorbic acid. The results of 3mM ascorbic acid in terms of sperm motility was better compared to control.…”
Section: Individual Motility Viability and Membrane Integritymentioning
confidence: 95%
“…Recently, Ali et al (2022) reported efficient cryopreservation of ringnecked pheasant semen with 3 mM ascorbic acid in extender, whereas higher concentrations were reported detrimental for all sperm parameters. These variations in effective levels of ascorbic acid in extender are indicative of variation in species sperm physiology.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, percent motility, viability, plasma membrane integrity and acrosomal intactness of fowl sperm were higher in extender supplemented with 2.0 mM ascorbic acid at all stages of cryopreservation, while higher level (0.4 mM) of ascorbic acid was detrimental in terms of post‐thaw sperm quality. Recently, Ali et al (2022) reported efficient cryopreservation of ring‐necked pheasant semen with 3 mM ascorbic acid in extender, whereas higher concentrations were reported detrimental for all sperm parameters. These variations in effective levels of ascorbic acid in extender are indicative of variation in species sperm physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation